Antarctic measurements of ozone by SAGE II in the spring of 1985, 1986, and 1987 - Mccormick, M. P.; Larsen, J. C. (1988)
This paper presents a three-year (1985, 1986, and 1987) comparison of ozone profiles within the southern polar vortex for September and October, using data obtained by the Stratospheric Aerosol and Gas Experiment II. It was found that, by the first half of October 1986, daily minima in total ozone showed a moderate recovery of 5-7 percent relative to 1985, whereas in 1987, a significant drop of 15 percent from the 1985 minima was observed. The interannual variability of total ozone, temperature, and temperature area or vortex size were found to display a quasi-biennial oscillation (QBO) signal similar to that established by Garcia and Solomon (1987) for Antarctica. Since the 1985 and 1987 years displayed the same QBO phase (westerly) and the 1987 depletion was greater than that of 1985, it is concluded that the long-term secular ozone trend continues to be downward.